Spatial Analysis and Multiple Regression Approach for Determining Soil Organic Material in Sampang Regency - Henny Pramoedyo; Ni Wayan Surya Wardhani; Eka Saraswati; Ria Rosilawati (Natural B, Journal of Health and Environmental Sciences, 2011)
An organic matter is one of the main components of soil. It is very potential to influence condition or type of soil and further it helps the growth of plants. One of methods which can be used to measure the levels of organic matters in an area is remote sensing technology and Geographic Information Systems (GIS) by using satellites. Analysis could be done in two steps. First, in statistically analysis by using regression models. The equation models of C-Organics level in -0,849 + 0,017X1 - 0.008X3 + 0.011X4.  Second, in spatial analysis, it is to know the C-Organic distribution, and also using interpolation with spatial analysis technique which is Inverse Distance Weighted (IDW) methods. Next, testing a model estimation which have been obtained in Sampang. Through the validation analysis using t-paired test, resulting estimation model which have been obtained is able to estimate the C-Organic levels in Sampang which could be an alternative way to estimate the C-Organic levels in same area.